Representasi Pluralisme Budaya dalam Sinetron Raden Kian Santang - Anwar Sobirin; Imam Syafi'i (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2020)
Cultural pluralism is the existence of more than one cultural system in a society, then the cultural system is equally enforced by members of the community. Cultural pluralism can arise because of the existence of various ethnic groups and also because of the process of community change. The focus of this research is how to represent cultural pluralism in the soap opera Raden Kian Santang. This study uses a qualitative approach with the type of research semiotics Roland Bartes. Data collection is done by observation, and documentation. Technical data analysis includes markers, markers, connotations and drawing conclusions. The results of the research from the representation of cultural pluralism in the soap opera Raden Kian Santang there are four points, namely. 1) It is not permissible to force a person to convert to the religion he adheres to, meaning that a person has the right to embrace the religion he believes in. 2) Not being hostile to other religions means that even though they are different religions, they still create a harmonious life and pray for each other for good things. 3) Help each other with fellow human beings. 4) Live in harmony and peace with fellow human beings. In this soap opera show, Raden Kian Santang represents how groups of people consisting of different cultures then they are in one group of royal society, able to accept each other without discriminating between one group and another. Several characters from different cultures in this show show the identity of their respective cultures. Among them are Hindu, Buddhist and Islamic cultures, however, figures from different cultures show an attitude of tolerance for each other. This can be seen from several characters of different cultures participating in the traditions of other cultures.